2019
DOI: 10.1002/cyto.b.21863
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow infiltration by flow cytometry at diffuse large B‐cell lymphoma NOS diagnosis implies worse prognosis without considering bone marrow histology

Abstract: Background: The significance of discrepant findings between histology (BMB) and flow cytometry (FC) in bone marrow (BM) examination at diffuse large B-cell lymphoma (DLBCL) diagnosis is uncertain. Methods: We performed a 5-year retrospective single-center study of patients diagnosed by DLBCL not otherwise specified (n = 82), divided into three groups according to BM infiltration at diagnosis: BMB−/FC− (75.6%), BMB+/FC+ (13.4%), and BMB−/FC+ (11%). Results: Median infiltration by FC analysis of the BMB−/FC+ gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Based on this finding, we speculate the complementary role between the two modalities. Although the prognostic association between BM involvement detection by biopsy and FCM has been controversial [ 18 , 19 , 20 , 27 ], our result indicated the combination of BM biopsy and FCM as the central component in BM analysis. BM smear and clot examinations are also useful modalities, as they may provide additional information and play the alternative role in some clinical situations.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Based on this finding, we speculate the complementary role between the two modalities. Although the prognostic association between BM involvement detection by biopsy and FCM has been controversial [ 18 , 19 , 20 , 27 ], our result indicated the combination of BM biopsy and FCM as the central component in BM analysis. BM smear and clot examinations are also useful modalities, as they may provide additional information and play the alternative role in some clinical situations.…”
Section: Discussionmentioning
confidence: 67%
“…Antigens examined included CD2, CD3, CD4, CD7, CD8, CD10, CD11c, CD16, CD19, CD20, CD23, CD25, CD34, CD45, CD56, kappa light chain, and lambda light chain. The presence of light chain restriction in B lymphoid cells was regarded as positive BM invasion [ 15 , 16 , 17 , 18 , 19 , 20 ]. BM aspirate smear specimen was subjected to Wright–Giemsa staining and 500 BM nucleated cells were cytologically evaluated to detect abnormal lymphoid cells under an optical microscope.…”
Section: Methodsmentioning
confidence: 99%
“…As described in the BMB/PET analysis, in one study [ 37 ], the agreement among FCM and PET rose from moderate (Cohen’s kappa index 0.54) to substantial (Cohen’s kappa index 0.74) after performing a second BM punction in patients with BMB−/PET+. The other study [ 43 ] reported a fair agreement between techniques (Cohen’s kappa index 0.3). Both articles agree in describing that approximately 70% of cases are both FCM/PET negative, while 8–14% are FCM+/PET+.…”
Section: Resultsmentioning
confidence: 91%
“…BMI is typically assessed by histologic and immunohistochemical (IHC) analysis of bone marrow biopsies and aspirations [ 5 ]; however, histopathological detection of BMI has limitations, notably the possibility of false‐negative results in cases with nontypical histomorphologic features, minimal BMI, or inadequate specimens. Immunophenotyping with flow cytometry and molecular studies using immunoglobulin (Ig) gene rearrangement can aid in determining the clonality of lymphoproliferative tissues [ 1 , 6 , 7 , 8 , 9 , 10 , 11 ]. Recent studies demonstrate that positron emission tomography (PET)/computed tomography (CT) may possess adequate sensitivity for BMI assessment in some diffuse large B‐cell lymphoma (DLBCL) cases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%